SAT0536 Multiple relapses in patients with giant cell arteritis. (12th June 2018) - Banjari, M.; LIOZON, E.; Dumonteil, S.; Gondran, G.; Palat, S.; Bezanahary, H.; Nadalon, S.; Fauchais, A.-L.; Ly, K.H.
Abstract : Background: Glucocorticoids (GC) remain the mainstay of treatment for patients with GCA. However, relapses and recurrences (events) occurred in 34% to 74.5% of the patients. 1–3 Most studies compared mainly patients with disease relapses/recurrences to whom without any. Objectives: To compare patients who had multiple events to those who presented only one in order to identify characteristics and predictive factors of multiple events in patient with GCA Methods: From 1976 to 2016, we collected prospectively clinical, laboratory, and pathological data, and the treatments and outcomes, of consecutive patients who were diagnosed to have GCA based ACR classification criteria. We compared these data in patients who had more than one event (group 1), either a relapse or a recurrence, to those who had only one (group 2). Relapse was defined as occurrence of clinical symptoms and/or inflammatory parameters, attributable to GCA, which required increased medication during follow-up i.e. under GC therapy while new disease activity after a period of remission was defined as a recurrence. Results: We included 494 patients for whom data was collected. Forty-seven patients were excluded from our cohort due to lack of data. Among the 447 patients, 228 (51%) presented at least one event. Mean age of this population was 73, 3±7 years with female predominance (70%). The median follow-up was 75±55 months. Among these patients 139 (61%) had only one event while 89 (39%) presented more than one. The total number of events was 477 of which 89 recurrences. Events occurred during the first year of treatment in 74% of patients. The majority of these events occurred with a mean prednisone dose of 12.8±9 mg/day (median dose 10 mg/d). In univariate analysis, significant differences between both groups is illustrated in table 1. Multivariate analysis showed that ear pain and an elevated ESR were predictive factors of multiple events (OR: 2, 45 and 1, 93; p=0, 04 and p=0, 03 respectively). We also found that this risk is lower in patients over 80 years-old (OR: 0, 35, p=0, 008) Conclusions: Patients with more than 1 event represent 7% to 46% of patients with event 1–3 which is consistent with our study (39%). The event occured most often during the first year of GC therapy in our cohort (74% of patients) while it affects 24% to 50% of patients in other series for the same period. 1–3 This difference could be explained by the heterogeneity of GC protocols. We did not found any positive correlation with hypertension, diabetes, and deep vein thrombosis that seemed to be more frequent in patients with multiple events. 2 In our study, this group of patients appeared younger and presented more oftently with cough, ear pain, and polymyalgia rheumatica that preceded GCA. Logically, in these patients, corticosteroid therapy was longer and the use of GC-sparing agent was more common. Although getting remission was more difficult in these patients, the long-term prognosis is not poor. References: [1] Restuccia, et al. Medicine2016. [2] Labarca, et al. Rheumatology2015. [3] Kermani, et al. J Rheumatol2015. Disclosure of Interest: None declared